Anonymous Proxy Server - Muhamad Yusof, Muhammad Fikri (Journal of Computing Technologies and Creative Content, 2019)
This Final Year Project is about Anonymous Proxy Server. The aim of this thesis is to implement multiple instances of Tor and Privoxy with Squid. With Tor users are able to preserve their identity on the internet such as IP address and location, and to evade internet censorship or blocked websites. This project was conducted using the Waterfall software development methodology that allows step by step approach in completing the project. It enables testing to be performed when all of the project’s requirement has been met. Something interesting that occurred was the multiple instances of Tor and Privoxy allows each window or tab of a browser to use different instances of Tor and Privoxy. This is a great deal since it allows the users to be able to have up to eight different IP addresses all coming from every parts of the world. Which means, they can be browsing two different websites at the same time and each website is being connected from somewhere else even though the users are only browsing in Malaysia.